HUBUNGAN TINGKAT PENGETAHUAN, SIKAP DAN PERILAKU REMAJA TERHADAP HIV/AIDS DI SMP-SMA ADVENT DOYO BARU JAYAPURA : RELATIONSHIPS ON THE LEVEL OF KNOWLEDGE, ATTITUDES AND BEHAVIOR OF YOUTH TOWARDS HIV / AIDS IN ADVENT HIGH SCHOOLS OF DOYO BARU JAYAPURA - Ayu Rombot (Jurnal Skolastik Keperawatan, 2021)
Human Immunodeficiency Virus (HIV) is a virus that damages the immune system by infecting and destroying CD4 cells. The more CD4 cells that are destroyed, the weaker the immune system will be, making it vulnerable to various diseases. and if HIV infection is not treated immediately it will develop into a serious condition called AIDS (Acquired Immune Deficiency Syndrome). The spread of HIV-AIDS is strongly influenced by factors of education, knowledge, attitudes and behavior. A person's knowledge of an object contains two aspects, namely the positive aspect and the negative aspect determining a person's attitude. This study aims to determine the relationship between the level of knowledge, attitudes and behavior of adolescents towards HIV / AIDS in Advend Doyo Baru Junior High School, Jayapura. The method used in this study is descriptive correlation with cross sectional approach, data collection techniques with total sampling of 200 students. Data analysis using the Likert scale test. The results obtained were students' knowledge of HIV / AIDS in the good category 45%, the students' good attitude towards HIV / AIDS was 50.5 and the students' behavior towards HIV / AIDS was 98.3%. The correlation test between students' knowledge, attitudes and behavior has a p value of 0.014 <0.119, this means that there is a significant relationship between knowledge and attitudes and behavior of students towards HIV / AIDS.